Microglia Susceptibility to Free Bilirubin Is Age-Dependent - Ana Rita Vaz; Ana Rita Vaz; Ana Sofia Falcão; Ana Sofia Falcão; Ana Sofia Falcão; Eleonora Scarpa; Carlotta Semproni; Dora Brites; Dora Brites (Frontiers Media S.A., 2020)
Increased concentrations of unconjugated bilirubin (UCB), namely its free fraction (Bf), in neonatal life may cause transient or definitive injury to neurons and glial cells. We demonstrated that UCB damages neurons and glial cells by compromising oligodendrocyte maturation and myelination, and by activating astrocytes and microglia. Immature neurons and astrocytes showed to be especially vulnerable. However, whether microglia susceptibility to UCB is also age-related was never investigated. We developed a microglia culture model in which cells at 2 days in vitro (2DIV) revealed to behave as the neonatal microglia (amoeboid/reactive cells), in contrast with those at 16DIV microglia that performed as aged cells (irresponsive/dormant cells). Here, we aimed to unveil whether UCB-induced toxicity diverged from the young to the long-cultured microglia. Cells were isolated from the cortical brain of 1- to 2-day-old CD1 mice and incubated for 24 h with 50/100 nM Bf levels, which were associated to moderate and severe neonatal hyperbilirubinemia, respectively. These concentrations of Bf induced early apoptosis and amoeboid shape in 2DIV microglia, while caused late apoptosis in 16DIV cells, without altering their morphology. CD11b staining increased in both, but more markedly in 2DIV cells. Likewise, the gene expression of HMGB1, a well-known alarmin, as well as HMGB1 and GLT-1-positive cells, were enhanced as compared to long-maturated microglia. The CX3CR1 reduction in 2DIV microglia was opposed to the 16DIV cells and suggests a preferential Bf-induced sickness response in younger cells. In conformity, increased mitochondrial mass and NO were enhanced in 2DIV cells, but unchanged or reduced, respectively, in the 16DIV microglia. However, 100 nM Bf caused iNOS gene overexpression in 2DIV and 16DIV cells. While only arginase 1/IL-1β gene expression levels increased upon 50/100 nM Bf treatment in long-maturated microglia, MHCII/arginase 1/TNF-α/IL-1β/IL-6 (>10-fold) were upregulated in the 2DIV microglia. Remarkably, enhanced inflammatory-associated microRNAs (miR-155/miR-125b/miR-21/miR-146a) and reduced anti-inflammatory miR-124 were found in young microglia by both Bf concentrations, while remained unchanged (miR/21/miR-125b) or decreased (miR-155/miR-146a/miR-124) in aged cells. Altogether, these findings support the neurodevelopmental susceptibilities to UCB-induced neurotoxicity, the most severe disabilities in premature babies, and the involvement of immune-inflammation neonatal microglia processes in poorer outcomes.